THE INFLUENCE OF THE MODE OF TOBACCO SEEDLINGS PRODUCTION OVER YIELD AND QUALITY OF TOBACCO - Romina Kabranova (My University, 2012)
The choice of appropriate technology in the production of healthy and high quality tobacco seedlings is a necessary step for obtaining high yield and quality with specific technological features. Tobacco Seedlings in Macedonia are still traditionally produced in improved cold outdoor beds and it is a labor intensive process, where obtaining quality seedlings is quite uncertain. Especially worrying is its acceptance after transplanting. For these reasons, investigations began to replace the traditional way of production with floating production (Float Tray System), a technology that has never been applied to oriental tobacco. Studies aimed to determine the impact of technology on the production of seedling growth and development of tobacco in the fields, on the resulting yield and on the quality. Two technologies were beeing compared: classical seedling production as a control-variant 1 and floating seedling production, with two variants of crystal NPK fertilizers with different amounts of nutrient elements (variant 2-N and variant 3-P) on two varieties of oriental tobacco (prilep NS 72 and yaka 125/3). The experiment was laid on the Veles Tabak Inc. fields in Veles, from 2007 till 2009. The results showed that the floating way of producing seedlings provides earlier transplantation of seedlings (within 4 days). Also, this gave better results in terms of quality of tobacco seedlings in relation to the dimensions of the plant, the total mass and their uniformity in size. After transplanting, tobacco seedlings originating from floating production have a higher percentage of acceptance, whereas the acceptance of variant 2-N is 93.4%. Yield of dry tobacco mass per unit area received from the tobacco seedling floating production (average of variants 2 and 3) is increased by 14% compared with variant 1, traditional production. Specifically, in variant 2-N the yield of tobacco is 21% and variant 3-P is 8.5% higher than the control variant, meaning that the fertilizer with higher nitrogen content favorably affected the yield. In terms of the quality of the acquired raw tobacco expressed through organoleptic evaluation of materials (visual and degustative) ranked varieties with the most points are: prilep NS 72 N with 96 points and yaka 125/3 N with 97 points, variant 2 floating production. Based on the results of chemical analysis of raw tobacco for major components it can be said that it is a quality resource of oriental tobacco. The highest industrial randman is the raw tobacco of floating variant-N, with 73.7% share of Unik 1-3 class in the total amount of tobacco. The most successful harvest was the one from 2009, when the share of integrated class Unik 1-3 is the highest (81%), average of all varieties. The highest economic impact was provided by tobacco raw material derived from the floating mode of production of tobacco seedlings which is 24% more in variant 2-N and 11% more in variant 3-P, compared with tobacco raw material obtained by traditional mode of production.
ВЛИЈАНИЕ НА НАЧИНОТ НА ПРОИЗВОДСТВО НА ТУТУНСКИ РАСАД ВРЗ ПРИНОСОТ И КВАЛИТЕТОТ НА ТУТУНОТ